Sestrin2 promotes LKB1‐mediated AMPK activation in the ischemic heart. Issue 2 (3rd November 2014) - Morrison, Alex; Chen, Li; Wang, Jinli; Zhang, Ming; Yang, Hui; Ma, Yina; Budanov, Andrei; Lee, Jun Hee; Karin, Michael; Li, Ji
ABSTRACT: The regulation of AMPK in the ischemic heart remains incompletely understood. Recent evidence implicates the role of Sestrin2 in the AMPK signaling pathway, and it is hypothesized that Sestrin2 plays an influential role during myocardial ischemia to promote AMPK activation. Sestrin2 protein was found to be expressed in adult cardiomyocytes and accumulated in the heart during ischemic conditions. Sestrin2 knockout (KO) mice were used to determine the importance of Sestrin2 during ischemia and reperfusion (I/R) injury. When wild‐type (WT) and Sestrin2 KO mice were subjected to in vivo I/R, myocardial infarct size was significantly greater in Sestrin2 KO compared with WT hearts. Similarly, Langendorff perfused hearts indicated exacerbated postischemic contractile function in Sestrin2 KO hearts compared with WT. Ischemic AMPK activation was found to be impaired in the Sestrin2 KO hearts. Immunoprecipitation of Sestrin2 demonstrated an association with AMPK. Moreover, liver kinase B1 (LKB1), a major AMPK upstream kinase, was associated with the Sestrin2‐AMPK complex in a time‐dependent manner during ischemia, whereas this interaction was nearly abolished in Sestrin2 KO hearts. Thus, Sestrin2 plays an important role in cardioprotection against I/R injury, serving as an LKB1‐AMPK scaffold to initiate AMPK activation during ischemic insults.—Morrison, A., Chen, L. Wang, J., Zhang, M., Yang, H., Ma, Y., Budanov, A., Lee, J. H., Karin, M., Li, J. Sestrin2 promotes LKB1‐mediated AMPK activation in the ischemic heart. FASEB J . 29, 408‐417 (2015). www.fasebj.org